Defining Moroccanness: the aesthetics and politics of contemporary Moroccan fashion design. Issue 1 (1st January 2016) - Jansen, M. Angela
Abstract : At the turn of the twenty-first century, a new generation of Moroccan fashion designers has started to emerge that can be distinguished from their predecessors by a radical style break. These designers no longer adhere to the idea that Moroccan fashion should be limited to a characteristic set of garments and/or decorations representing Arab-Muslim identity, but aspire an artistic freedom to conceptualise and define Moroccan fashion in an innovative, distinct and critical way. They are turning to Morocco's cultural diversity for inspiration, represented in popular culture, street styles, rural cultural heritage as well as the country's heterogeneous cultural past, including its African origins. This new generation, however, finds itself widely accused of 'not being Moroccan' by Moroccan consumers. I argue that this is due to the hegemonic construction of Moroccan national identity based on Arab-Muslim cultural heritage, dating back to the nationalist movement during the French Protectorate. What qualifies as Moroccan fashion – and especially as opposed to European fashion – in contemporary Moroccan urban society is complex and represents political, cultural and social power struggles. This style change initiated by contemporary designers not only reflects a general desire for more individual rights in relation to religious and cultural identity, but also a direct critique of the sociocultural domination of the elite. This article aims to analyse the aesthetics and politics of contemporary Moroccan fashion design and its artistic ambitions, as a way to challenge prevailing ideas of Moroccanness imposed by the ruling elite.